The Importance of Selecting Permanent Pacemaker, Evaluating the Heart and Assessing Quality of Life in Cardiac Patient - Ika Prasetya Wijaya (Interna Publishing, 2021)
The use of pacemakers is necessary for patients with symptomatic bradycardia. Pacemaker implantation also acts as a life-saving procedure. However, there are several reports that patients with a pacemaker (the most widely used pacemaker is on the right ventricle, known as single chamber pacemaker) had disturbances in left ventricle contraction lead to left ventricular systolic dysfunction. Global Longitudinal Strain (GLS) Echocardiography can confirm these left ventricular disturbances. Echocardiography examination is best carried out before and after single-chamber PPM implantation. This study compares PPM placement in apical Right Ventricle (RV) and Right Ventricular Outflow Tract (RVOT) and compares paced QRS duration 150 ms and > 150 ms. Pacing burden >40% causes subclinical left ventricular systolic dysfunction after a month of PPM implantation with decreased GLS in apical RV pacing. This study gives additional information that PPM placement is preferably in RVOT with some specific settings. However, there are many ways to reduce the effects of impaired left ventricular function due to lead installation on the PPM single-chamber device. By using the PPM device which has a dual chamber, the leads will be placed in RVOT and also in the right atrium with atrial-ventricle synchronization. The aim is to avoid impaired left ventricular pump function as supported by a systematic review which states the superiority of dual-chamber PPM over single-chamber PPM in reducing atrial fibrillation and pacemaker syndrome. In the importance of quality of life related to heart disease, the Indonesian version of the MacNew questionnaire can be used. This questionnaire seeks the quality of life of patients with coronary heart disease after revascularization surgery and has undergone rehabilitation. Another important thing is the suitability of the adaptation to the original English version.